Autosomal Recessive Rod-Cone Dystrophy Associated With Compound Heterozygous Variants in ARL3 Gene - Fu, Leming; Li, Ya; Yao, Shun; Guo, Qingge; You, Ya; Zhu, Xianjun; Lei, Bo (Frontiers in Cell and Developmental Biology, 2021)
Purpose:ARL3 (ADP-ribosylation factor-like 3) variants cause autosomal dominant retinitis pigmentosa (RP) or autosomal recessive Joubert syndrome. We found a family with rod-cone dystrophy (RCD) and verified it was associated with compound heterozygous variants in ARL3 gene. Methods: Ophthalmic examinations including optical coherence tomography and electroretinogram (ERG) were performed. Targeted next generation sequencing (NGS) was performed for the proband using a custom designed panel. Sanger sequencing and co-segregation were conducted in the family members. Changes of protein structure mediated by the variants were studied in vitro. ARL3 protein stability and its interaction with RP2 protein were assessed by cycloheximide chase assay and co-immunoprecipitation (Co-IP) assay. Results: Visual acuity of the 18-year-old male proband was 0.25 in the right and 0.20 in the left eye, while his non-consanguineous parents and sister was normal. The proband showed signs of RCD, including nyctalopia, peripheral field loss, bone-spicule deposits in the retina, and reduced ERG responses. The father, aged 50 years old, showed visual acuity of 1.0 in both eyes. Unlike the proband, he presented late onset and mild cone-rod dystrophy (CRD), including macular atrophy, central scotomata, moderate reduction in photopic ERG responses. None of all the family members had hearing abnormality, mental dysplasia or gait instability. We identified two novel compound heterozygous variants (c.91A>G, p.T31A; c.353G>T, p.C118F) in ARL3 in the proband, while his father only had variant c.91A>G. Bioinformatics analysis indicated amino acid positions of the two variants are highly conserved among species. The in silico tools predicted the variants to be harmful. Protein structure analysis showed the two variants had potential to alter the protein structure. Based on the ACMG guidelines, the two variants were likely pathogenic. In addition, the ARL3 mutations destabilized ARL3 protein, and the mutation c.353G>T disrupted the interaction between ARL3 and RP2 in HEK293T cells. Conclusions: We showed novel compound heterozygous variants in ARL3 were associated with early onset of autosomal recessive RCD, while c.91A>G along may be associated with a late onset of dominant CRD. The two variants in ARL3 could be causative by destabilizing ARL3 protein and impairing its interaction with RP2 protein.